Heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste as well as preparation method and application of heavy metal ion sealing and anti-dispersion grouting material

By mixing coal-based solid waste with specific additives in a specific proportion, heavy metal ion solid sealing and anti-dispersion grouting materials are prepared, which solves the problems of solid sealing and anti-dispersion properties of heavy metal ions in coal-based solid waste, and improves the environmental safety and long-term stability of the material.

CN119735423AActive Publication Date: 2025-04-01ANHUI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510066619.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-01
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

The prior art is difficult to effectively fix heavy metal ions in coal-based solid waste, prevent them from migrating and diffusion in soil and groundwater, while maintaining the performance of resistant to dispersion grouting materials.

Method used

By mixing coal-based solid waste, coal-based solid-sealing and anti-dispersion grouting materials in specific proportions, heavy metal ion solid-sealing and anti-dispersion grouting materials are prepared. This material forms a stable structure through the action of an alkali exciter, effectively fixes heavy metal ions, and maintains good anti-dispersion properties.

Benefits of technology

It significantly improves the environmental safety and long-term stability of the grouting material, effectively fixes heavy metal ions, prevents them from migrating and diffusion, enhances the material's resistance to dispersion and cementation, extends the service life of the material, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735423A_ABST
    Figure CN119735423A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solid waste recycling, and provides a heavy metal ion sealing and dispersion-resistant grouting material based on coal-based solid waste and a preparation method and application thereof.The preparation method comprises the steps that a base material composed of coal gangue, fly ash, silica fume, cellulose, bentonite and a water reducing agent is prepared through a base material preparation step; an alkali activator is prepared through an alkali activator preparation step, and the heavy metal ion sealing and dispersion-resistant grouting material based on the coal-based solid waste is prepared by adopting the prepared basic material and the alkali activator. According to the heavy metal ion sealing and dispersion-resistant grouting material based on the coal-based solid waste and the preparation method and application thereof, the environmental safety, long-term stability and dispersion resistance of the grouting material can be remarkably improved, the environmental benefits of solid waste treatment and pollution prevention and control are effectively improved, and the production cost is effectively reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid waste recycling, and in particular to a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste, and a preparation method and application thereof. Background Art

[0002] Coal-based solid waste is an inevitable byproduct of my country's coal industry production. Its production volume is huge. Long-term accumulation not only occupies a large amount of land resources, but also may cause environmental pollution, such as soil pollution and groundwater pollution. With the increasing requirements for environmental protection, the resource utilization of coal-based solid waste has gradually become an important research field. By converting coal-based solid waste into useful materials, it can not only effectively reduce its burden on the environment, but also realize its economic value, which has important practical significance.

[0003] Anti-dispersion grouting materials play a key role in many engineering fields. This type of material mainly refers to materials that can remain stable and avoid dispersion during the grouting process, and are often used in underground engineering, mine reinforcement, soil improvement and other fields. Good fluidity and stability are important performance indicators of anti-dispersion grouting materials. They can ensure that the grouting materials flow smoothly and fill evenly in complex underground environments, thereby achieving the purpose of reinforcement and improvement. However, traditional cement grouting materials have obvious shortcomings. They have poor fluidity and are prone to dispersion during the grouting process, which not only affects the grouting effect, but may also lead to material waste and engineering quality problems. Therefore, researchers have been committed to developing anti-dispersion grouting materials with better performance to meet the growing engineering needs.

[0004] Applying coal-based solid waste to grouting materials is a pioneering new field. In practical applications, there are the following technical bottlenecks: 1. Coal-based solid waste contains heavy metal ions such as copper, lead, cadmium, mercury, and chromium, which are highly toxic and penetrate into the soil and groundwater during the grouting process, causing serious environmental pollution and posing a huge threat to the ecosystem and human health; 2. There is a lack of effective sealing technology to fix heavy metal ions in the material to prevent their migration and diffusion; 3. In the process of fixing heavy metal ions, it will have an adverse effect on the anti-dispersion performance of the grouting material, resulting in the material being unable to meet the requirements of actual engineering applications.

[0005] Therefore, how to develop a grouting material that can effectively fix heavy metal ions and maintain good anti-dispersion properties on the basis of realizing the resource utilization of coal-based solid waste is a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of this, in order to overcome the deficiencies of the prior art, the present application aims to provide a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste, and a preparation method and application thereof.

[0007] According to the first aspect of the present application, a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste is provided, wherein the material is made of coal gangue, fly ash, silica fume, cellulose, bentonite, a water reducer and an alkali activator.

[0008] According to the second aspect of the present application, a method for preparing a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste is provided. The preparation method includes a base material preparation step, an alkali activator preparation step and a grouting material preparation step. The base material preparation step is used to prepare a base material composed of coal gangue, fly ash, silica fume, cellulose, bentonite and a water reducer. The alkali activator preparation step is used to prepare an alkali activator. The prepared base material and alkali activator are used to prepare the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste.

[0009] Optionally, in the preparation method of heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste of the present application, the weight parts of each reactant of the base material are as follows: 100-400 weight parts of coal gangue, 250-400 weight parts of fly ash, 350-500 weight parts of silica ash, 7.5 weight parts of cellulose, 100 weight parts of bentonite, and 5 weight parts of water reducer.

[0010] Optionally, in the method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste of the present application, the weight parts of the alkaline activator reactants are as follows: 537.9 weight parts of deionized water, 42.14 weight parts of sodium hydroxide, and 320 weight parts of water glass.

[0011] Optionally, the present invention provides a method for preparing a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste, comprising the following steps: The coal gangue, fly ash, silica fume, cellulose, bentonite and water reducing agent are mixed and stirred to obtain a base material; Sodium hydroxide and water glass are added into deionized water, and an alkali activator is prepared by stirring. An alkali activator is added into the base material, and the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste is prepared through stirring treatment.

[0012] Optionally, in the method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste of the present application, the bulk density of the water reducer is 500-550 g / L, the solid content is greater than 98%, and the water reduction rate is greater than 15%.

[0013] Optionally, in the method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste of the present application, the main chain of cellulose is composed of glucose units connected by β-1,4-glycosidic bonds.

[0014] Optionally, in the method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste of the present application, the cellulose is hydroxyethyl methyl cellulose.

[0015] Optionally, in the method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste of the present application, the modulus of water glass is 3.2, the solid content is 40%, the Baume degree is 40, and the pH value is 9.

[0016] According to the third aspect of the present application, an application of heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste is provided, and the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared according to the method of the second aspect of the present application are used as grouting materials for soil filling projects.

[0017] The heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste and its preparation method and application have the following beneficial technical effects: 1. Significantly improve the environmental safety of grouting materials, enhance the sealing effect of heavy metal ions, use sealing technology to effectively fix heavy metal ions in coal-based solid waste, prevent the migration and diffusion of heavy metal ions in groundwater and soil, and significantly reduce the risk of heavy metal pollution. The material will not release harmful heavy metal ions during use, thereby ensuring the quality of soil and water, making it more reliable in various application scenarios, especially in underground projects with high environmental requirements, and can better meet environmental protection standards.

[0018] 2. Significantly improve the long-term stability of grouting materials. Not only does it improve the environmental stability of the material through the sealing technology, but it also enhances the bonding and strength of the material through the component ratio, so that the material can effectively maintain its own stability in complex underground environments, such as when facing factors such as water flow and soil movement, and avoid material dispersion or loss, thereby ensuring its long-term and stable application in underground projects and extending the service life of the material.

[0019] 3. Significantly improve the anti-dispersion property of grouting materials, so that the materials can resist external forces such as water erosion and soil extrusion in complex underground environments, such as areas with abundant groundwater or areas with frequent soil movement, maintain the integrity and continuity of the materials, and further improve their safe application performance in underground projects, providing a strong guarantee for the stability of underground projects and reducing the cost of engineering maintenance and reconstruction caused by poor material performance.

[0020] 4. Effectively improve the environmental benefits of solid waste treatment and pollution prevention and control. Using coal-based solid waste as the main raw material effectively solves the environmental pollution problem caused by the accumulation of coal-based solid waste, avoids the pollution of land, air and water caused by its long-term accumulation, reduces the burden of solid waste on the environment, and realizes the recycling of resources.

[0021] 5. Reduce production costs, use coal-based solid waste as the main raw material, make full use of the waste that originally needed to be processed, reduce dependence on traditional raw materials, and improve economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0023] Figure 1 XRD spectra of coal gangue, fly ash, silica fume and bentonite used in Examples 1 to 8 of the present application; Figure 2 A schematic diagram of the heavy metal ion sealing effect of the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 4 of the present application; Figure 3 A schematic diagram of the heavy metal ion sealing effect of the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 5 to 8 of the present application; Figure 4 This is a scanning electron microscope image of the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste prepared in Example 1 of the present application; Figure 5 This is a scanning electron microscope image of the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste prepared in Example 5 of the present application; Figure 6 This is a Fourier transform infrared spectrum of the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste prepared in Examples 1 and 5 of the present application. DETAILED DESCRIPTION

[0024] The embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0025] It should be noted that the following embodiments and features in the embodiments may be combined with each other in the absence of conflict; and, based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making any creative work are within the scope of protection of the present disclosure.

[0026] It should be noted that various aspects of the embodiments within the scope of the appended claims are described below. It should be apparent that the aspects described herein may be embodied in a wide variety of forms, and any specific structure and / or function described herein is merely illustrative. Based on the present disclosure, it should be understood by those skilled in the art that an aspect described herein may be implemented independently of any other aspect, and two or more of these aspects may be combined in various ways. For example, any number of aspects described herein may be used to implement the device and / or practice the method. In addition, other structures and / or functionalities other than one or more of the aspects described herein may be used to implement this device and / or practice this method.

[0027] The coal gangue, fly ash, silica fume and bentonite of Examples 1 to 8 of the present application were analyzed by Shimadzu XRD-6000, with a test angle of 5°-80° and a test speed of 5° / min. Figure 1 These are the XRD spectra of coal gangue, fly ash, silica fume and bentonite used in Examples 1 to 8 of the present application.

[0028] Example 1 Preparation of heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste: Step 1: Preparation of base materials 100 parts by weight of coal gangue, 400 parts by weight of fly ash, 500 parts by weight of silica fume, 7.5 parts by weight of cellulose, and 5 parts by weight of water reducer are mixed and stirred for 5 minutes to obtain a base material. In this embodiment, the bulk density of the water reducer is 500-550 g / L, the solid content is greater than 98%, and the water reduction rate is greater than 15%. The main chain of cellulose is composed of glucose units connected by β-1,4-glycosidic bonds, for example, cellulose is hydroxyethyl methyl cellulose.

[0029] Step 2: Preparation of alkaline activator 42.14 parts by weight of sodium hydroxide and 320 parts by weight of water glass were added to 537.9 parts by weight of deionized water, and stirred for 3 minutes to prepare an alkali activator. In this embodiment, the modulus of the water glass was 3.2, the solid content was 40%, the Baume degree was 40, and the pH value was 9.

[0030] Step 3: Preparation of grouting materials The alkaline activator prepared in step three is added to the base material prepared in step one, and stirred for 3 minutes to obtain a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste.

[0031] Example 2 Preparation of heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste: Step 1: Preparation of base materials 200 parts by weight of coal gangue, 350 parts by weight of fly ash, 450 parts by weight of silica fume, 7.5 parts by weight of cellulose and 5 parts by weight of water reducer are mixed and stirred for 5 minutes to obtain a base material. In this embodiment, the bulk density of the water reducer is 500-550 g / L, the solid content is greater than 98%, and the water reduction rate is greater than 15%. The main chain of cellulose is composed of glucose units connected by β-1,4-glycosidic bonds, for example, cellulose is hydroxyethyl methyl cellulose.

[0032] Step 2: Preparation of alkaline activator 42.14 parts by weight of sodium hydroxide and 320 parts by weight of water glass were added to 537.9 parts by weight of deionized water, and stirred for 3 minutes to prepare an alkali activator. In this embodiment, the modulus of the water glass was 3.2, the solid content was 40%, the Baume degree was 40, and the pH value was 9.

[0033] Step 3: Preparation of grouting materials The alkaline activator prepared in step three is added to the base material prepared in step one, and stirred for 3 minutes to obtain a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste.

[0034] Example 3 Preparation of heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste: Step 1: Preparation of base materials 300 parts by weight of coal gangue, 300 parts by weight of fly ash, 400 parts by weight of silica fume, 7.5 parts by weight of cellulose and 5 parts by weight of water reducer are mixed and stirred for 5 minutes to obtain a base material. In this embodiment, the bulk density of the water reducer is 500-550 g / L, the solid content is greater than 98%, and the water reduction rate is greater than 15%. The main chain of cellulose is composed of glucose units connected by β-1,4-glycosidic bonds, for example, cellulose is hydroxyethyl methyl cellulose.

[0035] Step 2: Preparation of alkaline activator 42.14 parts by weight of sodium hydroxide and 320 parts by weight of water glass were added to 537.9 parts by weight of deionized water, and stirred for 3 minutes to prepare an alkali activator. In this embodiment, the modulus of the water glass was 3.2, the solid content was 40%, the Baume degree was 40, and the pH value was 9.

[0036] Step 3: Preparation of grouting materials The alkaline activator prepared in step three is added to the base material prepared in step one, and stirred for 3 minutes to obtain a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste.

[0037] Example 4 Preparation of heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste: Step 1: Preparation of base materials 400 parts by weight of coal gangue, 250 parts by weight of fly ash, 350 parts by weight of silica fume, 7.5 parts by weight of cellulose and 5 parts by weight of water reducer are mixed and stirred for 5 minutes to obtain a base material. In this embodiment, the bulk density of the water reducer is 500-550 g / L, the solid content is greater than 98%, and the water reduction rate is greater than 15%. The main chain of cellulose is composed of glucose units connected by β-1,4-glycosidic bonds, for example, cellulose is hydroxyethyl methyl cellulose.

[0038] Step 2: Preparation of alkaline activator 42.14 parts by weight of sodium hydroxide and 320 parts by weight of water glass were added to 537.9 parts by weight of deionized water, and stirred for 3 minutes to prepare an alkali activator. In this embodiment, the modulus of the water glass was 3.2, the solid content was 40%, the Baume degree was 40, and the pH value was 9.

[0039] Step 3: Preparation of grouting materials The alkaline activator prepared in step three is added to the base material prepared in step one, and stirred for 3 minutes to obtain a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste.

[0040] Example 5 Preparation of heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste: Step 1: Preparation of base materials 100 parts by weight of coal gangue, 400 parts by weight of fly ash, 500 parts by weight of silica fume, 7.5 parts by weight of cellulose, 100 parts by weight of bentonite and 5 parts by weight of water reducer are mixed and stirred for 5 minutes to obtain a base material. In this embodiment, the bulk density of the water reducer is 500-550 g / L, the solid content is greater than 98%, and the water reduction rate is greater than 15%. The main chain of cellulose is composed of glucose units connected by β-1,4-glycosidic bonds, for example, cellulose is hydroxyethyl methyl cellulose.

[0041] Step 2: Preparation of alkaline activator 42.14 parts by weight of sodium hydroxide and 320 parts by weight of water glass were added to 537.9 parts by weight of deionized water, and stirred for 3 minutes to prepare an alkali activator. In this embodiment, the modulus of the water glass was 3.2, the solid content was 40%, the Baume degree was 40, and the pH value was 9.

[0042] Step 3: Preparation of grouting materials The alkaline activator prepared in step three is added to the base material prepared in step one, and stirred for 3 minutes to obtain a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste.

[0043] Example 6 Preparation of heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste: Step 1: Preparation of base materials 200 parts by weight of coal gangue, 350 parts by weight of fly ash, 450 parts by weight of silica fume, 7.5 parts by weight of cellulose, 100 parts by weight of bentonite and 5 parts by weight of water reducer are mixed and stirred for 5 minutes to obtain a base material. In this embodiment, the bulk density of the water reducer is 500-550g / L, the solid content is greater than 98%, and the water reduction rate is greater than 15%. The main chain of cellulose is composed of glucose units connected by β-1,4-glycosidic bonds, for example, cellulose is hydroxyethyl methyl cellulose.

[0044] Step 2: Preparation of alkaline activator 42.14 parts by weight of sodium hydroxide and 320 parts by weight of water glass were added to 537.9 parts by weight of deionized water, and stirred for 3 minutes to prepare an alkali activator. In this embodiment, the modulus of the water glass was 3.2, the solid content was 40%, the Baume degree was 40, and the pH value was 9.

[0045] Step 3: Preparation of grouting materials The alkaline activator prepared in step three is added to the base material prepared in step one, and stirred for 3 minutes to obtain a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste.

[0046] Example 7 Preparation of heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste: Step 1: Preparation of base materials 300 parts by weight of coal gangue, 300 parts by weight of fly ash, 400 parts by weight of silica fume, 7.5 parts by weight of cellulose, 100 parts by weight of bentonite and 5 parts by weight of water reducer are mixed and stirred for 5 minutes to obtain a base material. In this embodiment, the bulk density of the water reducer is 500-550 g / L, the solid content is greater than 98%, and the water reduction rate is greater than 15%. The main chain of cellulose is composed of glucose units connected by β-1,4-glycosidic bonds, for example, cellulose is hydroxyethyl methyl cellulose.

[0047] Step 2: Preparation of alkaline activator 42.14 parts by weight of sodium hydroxide and 320 parts by weight of water glass were added to 537.9 parts by weight of deionized water, and stirred for 3 minutes to prepare an alkali activator. In this embodiment, the modulus of the water glass was 3.2, the solid content was 40%, the Baume degree was 40, and the pH value was 9.

[0048] Step 3: Preparation of grouting materials The alkaline activator prepared in step three is added to the base material prepared in step one, and stirred for 3 minutes to obtain a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste.

[0049] Example 8 Preparation of heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste: Step 1: Preparation of base materials 400 parts by weight of coal gangue, 250 parts by weight of fly ash, 150 parts by weight of silica fume, 7.5 parts by weight of cellulose, 100 parts by weight of bentonite and 5 parts by weight of water reducer are mixed and stirred for 5 minutes to obtain a base material. In this embodiment, the bulk density of the water reducer is 500-550 g / L, the solid content is greater than 98%, and the water reduction rate is greater than 15%. The main chain of cellulose is composed of glucose units connected by β-1,4-glycosidic bonds, for example, cellulose is hydroxyethyl methyl cellulose.

[0050] Step 2: Preparation of alkaline activator 42.14 parts by weight of sodium hydroxide and 320 parts by weight of water glass were added to 537.9 parts by weight of deionized water, and stirred for 3 minutes to prepare an alkali activator. In this embodiment, the modulus of the water glass was 3.2, the solid content was 40%, the Baume degree was 40, and the pH value was 9.

[0051] Step 3: Preparation of grouting materials The alkaline activator prepared in step three is added to the base material prepared in step one, and stirred for 3 minutes to obtain a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste.

[0052] Example 9 The initial setting time and final setting time of the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 8 were measured using an ISO standard Vicat instrument.

[0053] The fluidity of the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 8 was measured. The flow test apparatus was a standard truncated cone mold (upper opening diameter of 36 mm, lower opening diameter of 60 mm, height of 60 mm) and a glass plate.

[0054] The dynamic water retention rate of the heavy metal ion encapsulation and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 8 was measured using an anti-dispersion test device.

[0055] The initial setting time, final setting time, fluidity and dynamic water retention rate of the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 8 are measured and are shown in Table 1 below.

[0056] Table 1

[0057] The present application locks moisture inside the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste through a comprehensive design of the component ratio, and expands it to form a network structure. While enhancing the anti-dispersion and stability of the material, it increases the dynamic water retention rate and the adhesion of the material, making it difficult for moisture to be lost from the slurry.

[0058] As shown in Table 1, the heavy metal ion encapsulation and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 8 of the present application have a wide range of initial setting time, final setting time and fluidity, and can be used to prepare engineering permanent grouting materials with excellent anti-dispersion and stability according to actual application scenarios. It should be noted that the dynamic water retention rate of the heavy metal ion encapsulation and anti-dispersion grouting materials based on coal-based solid waste prepared in the examples of the present application is not less than 80%, and the dynamic water retention rates of the heavy metal ion encapsulation and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 5 to 7 are all higher than 99%.

[0059] The heavy metal ion content of the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 8 was measured using an inductively coupled plasma emission spectrometer. The test results of the inductively coupled plasma emission spectrometer are shown in Table 2.

[0060] Table 2

[0061] Note: “ND” means the item was not detected.

[0062] The heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 8 of the present application were observed by leaching test, and the sealing of the slurry in deionized water was observed. The results are as follows: Figure 2 and Figure 3 shown.

[0063] In the present application, the solubility or chemical form of metal ions is adjusted and controlled through component ratio and process design, thereby improving the fixation or inhibition effect of metal ions. Figure 2 A schematic diagram of the heavy metal ion sealing effect of the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 4 of the present application; Figure 3 Schematic diagram of the heavy metal ion sealing effect of the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 5 to 8 of the present application. Figure 2 and Figure 3It can be seen that the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Examples 1 to 8 of the present application achieve a large specific surface area and negative charge inside the system through component design, and adsorb heavy metal ions.

[0064] The surface morphology of the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Example 1 and Example 5 was analyzed using Hitachi S-4800. Figure 4 This is a scanning electron microscope image of the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste prepared in Example 1 of the present application; Figure 5 This is a scanning electron microscope image of the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste prepared in Example 5 of the present application.

[0065] like Figure 4 As shown, the coal-based solid waste-based heavy metal ion sealing and anti-dispersion grouting material prepared in Example 1 has a dense microstructure, a certain amount of crystal morphology and irregular clusters, a clear interface between particles, and obvious flaky and layered features on the particle surface. The dense structure significantly improves the corrosion resistance and has the effect of long-term sealing of heavy metal ions. Figure 5 As shown, the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste prepared in Example 5 has large pores and a needle-rod structure, large gaps between particles, a relatively loose system structure, good adsorption capacity, and provides more adsorption sites for heavy metal ions.

[0066] The Thermo Scientific Nicolet iS50 instrument was used to detect the absorption of infrared radiation of different wavelengths for the heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste prepared in Example 1 and Example 5. Figure 6 This is a Fourier transform infrared spectrum of the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste prepared in Examples 1 and 5 of the present application.

[0067] like Figure 6 As shown, from the CH stretching vibration peak (1470 cm -1), the absorption peak of the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste prepared in Example 1 is relatively weak, and the carbonate peak is relatively weak, indicating that the carbonization degree of the material is relatively low, which is conducive to the formation of stable hydration products. The heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste prepared in Example 5 has a relatively strong carbonate characteristic peak, indicating that the component ratio of Example 5 forms more carbonates, thereby promoting the reaction between heavy metal ions and carbonates and improving the sealing performance. In addition, the cations between the bentonite layers can exchange with heavy metal ions to further fix the heavy metal ions. During the sealing process, this cation exchange has a strong physical adsorption capacity, which helps to further enhance the stable sealing effect of heavy metal ions.

[0068] The heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste and the preparation method thereof according to the embodiments of the present application have the following beneficial technical effects: 1. Significantly improve the environmental safety of grouting materials, enhance the sealing effect of heavy metal ions, use sealing technology to effectively fix heavy metal ions in coal-based solid waste, prevent the migration and diffusion of heavy metal ions in groundwater and soil, and significantly reduce the risk of heavy metal pollution. The material will not release harmful heavy metal ions during use, thereby ensuring the quality of soil and water, making it more reliable in various application scenarios, especially in underground projects with high environmental requirements, and can better meet environmental protection standards.

[0069] 2. Significantly improve the long-term stability of grouting materials. Not only does it improve the environmental stability of the material through the sealing technology, but it also enhances the bonding and strength of the material through the component ratio, so that the material can effectively maintain its own stability in complex underground environments, such as when facing factors such as water flow and soil movement, and avoid material dispersion or loss, thereby ensuring its long-term and stable application in underground projects and extending the service life of the material.

[0070] 3. Significantly improve the anti-dispersion property of grouting materials, so that the materials can resist external forces such as water erosion and soil extrusion in complex underground environments, such as areas with abundant groundwater or areas with frequent soil movement, maintain the integrity and continuity of the materials, and further improve their safe application performance in underground projects, providing a strong guarantee for the stability of underground projects and reducing the cost of engineering maintenance and reconstruction caused by poor material performance.

[0071] 4. Effectively improve the environmental benefits of solid waste treatment and pollution prevention and control. Using coal-based solid waste as the main raw material effectively solves the environmental pollution problem caused by the accumulation of coal-based solid waste, avoids the pollution of land, air and water caused by its long-term accumulation, reduces the burden of solid waste on the environment, and realizes the recycling of resources.

[0072] 5. Reduce production costs, use coal-based solid waste as the main raw material, make full use of the waste that originally needed to be processed, reduce dependence on traditional raw materials, and improve economic benefits.

[0073] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. Heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste, characterized in that: The material is prepared from coal gangue, fly ash, silica ash, cellulose, bentonite, water reducing agent and alkali activator.

2. A method for preparing a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste, characterized in that: The preparation method comprises a base material preparation step, an alkali activator preparation step and a grouting material preparation step. The base material preparation step is used to prepare a base material composed of coal gangue, fly ash, silica fume, cellulose, bentonite and a water reducer. The alkali activator preparation step is used to prepare an alkali activator. The prepared base material and alkali activator are used to prepare a heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste.

3. The method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste according to claim 2, characterized in that: The weight parts of each reactant of the base material are as follows: 100-400 weight parts of coal gangue, 250-400 weight parts of fly ash, 350-500 weight parts of silica fume, 7.5 weight parts of cellulose, 100 weight parts of bentonite, and 5 weight parts of water reducing agent.

4. The method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste according to claim 2, characterized in that: The weight parts of the alkaline activator reactants are as follows: 537.9 weight parts of deionized water, 42.14 weight parts of sodium hydroxide, and 320 weight parts of water glass.

5. The method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste according to claim 2, characterized in that: The preparation method comprises the following steps: The coal gangue, fly ash, silica fume, cellulose, bentonite and water reducing agent are mixed and stirred to obtain a base material; Sodium hydroxide and water glass are added into deionized water, and an alkali activator is prepared by stirring. An alkali activator is added into the base material, and the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste is prepared through stirring treatment.

6. The method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste according to claim 5, characterized in that: The bulk density of the water reducer is 500-550g / L, the solid content is greater than 98%, and the water reduction rate is greater than 15%.

7. The method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste according to claim 5, characterized in that: The main chain of cellulose is composed of glucose units connected by β-1,4-glycosidic bonds.

8. The method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste according to claim 5, characterized in that: The cellulose is hydroxyethyl methyl cellulose.

9. The method for preparing heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste according to claim 5, characterized in that: The modulus of water glass is 3.2, the solid content is 40%, the Baume degree is 40, and the pH value is 9.

10. Application of heavy metal ion sealing and anti-dispersion grouting materials based on coal-based solid waste, characterized in that: Application of the heavy metal ion sealing and anti-dispersion grouting material based on coal-based solid waste prepared by the method described in any one of claims 2 to 9 as a grouting material for soil filling projects.

Citation Information

Patent Citations

  • Dispersion-resistant and high-impermeability grouting material under flowing water condition as well as preparation method and application thereof

    CN115504747A

  • Environment-friendly underground water pollution channel blocking material as well as preparation method and application thereof

    CN117865637A